The Effect of Learning Quality And Learning Satisfaction on Learning Outcomes in Online Learning - Nailis Sa’adah; Taufik Hidayat (International Conference on Multidisciplinary Research, 2022)
The Covid-19 pandemic has started to hit Indonesia since 2020. The government has implemented online learning for all levels of education to suppress the spread of the virus. There are many differences that students feel when participating in online learning. This study aims to determine the effect of the quality of learning and the learning process on learning outcomes during the implementation of online learning at the Department of Computer Engineering, University of Serambi Mecca. The survey was conducted using a descriptive method. The survey was carried out by distributing questionnaires to be filled in by students of the Computer Engineering Department who had attended online lecture activities. Survey data analysis was carried out using the Linear Regression Method. Based on the results of the analysis, it was obtained a Sig value > 0.05 where partially the variable quality of learning and learning satisfaction did not have a significant effect on the variable Learning Outcomes. The RSquare value is 0.021 or 2.1%. This means that this model can only explain 2.1% of the effect of the variable and the rest is influenced by other variables not examined in this study. Keywords: Online Learning, Linear Regresion Method, Survey.